Ectopic mediastinal parathyroid adenoma - Caporale, D.M.S.; Bobbio, A.; Accordino, et al., R. (Acta Biomedica Atenei Parmensis, 2003)
Ectopic mediastinal parathyroid adenomas may be cause of Primary Hyperparathyroidism (PH). The occurrence of these lesions is explainable on embryologic basis.We report the case of a 20-year-old patient with PH due to an ectopic mediastinal parathyroid adenoma located in the anterior mediastinum. After its accurate pre-operative localization, surgical resection through a cervical manubriotomy was performed. Serum calcium and parathyroid hormone (PTH) levels returned promptly within the normal range, no complications occurred and the patient was discharged in the 4th postoperative day. Different surgical approaches are discussed.